Transgenic Chlamydomonas Expressing Human Transient Receptor Potential Ankyrin 1 (TRPA1) Channels to Assess the Effect of Agonists and Antagonists - Yoshida, Megumi; Yamamiya, Ryodai; Shimizu, Yuto; Yoshimura, Kenjiro (Frontiers in Pharmacology, 2020)
Transient receptor potential channel ankyrin 1 (TRPA1) is an ion channel whose gating is controlled by agonists, such as allyl isothiocyanate (AITC), and temperature. Since TRPA1 is associated with various disease symptoms and chemotherapeutic side effects, it is a frequent target of drug development. To facilitate the screening of TRPA1 agonists and antagonists, this study aimed to develop a simple bioassay for TRPA1 activity. To this end, transgenic Chlamydomonas reinhardtii expressing human TRPA1 was constructed. The transformants exhibited positive phototaxis at high temperatures (≥20ºC) but negative phototaxis at low temperatures (≤15ºC); wild-type cells showed positive phototaxis at all temperatures examined. In transgenic cells, negative phototaxis was inhibited by TRPA1 antagonists, such as HC030031, A-967079, and AP18, at low temperatures. Negative phototaxis was induced by TRPA1 agonists, such as icilin and AITC, at high temperatures. The effects of these agonists were blocked by TRPA1 antagonists. In wild-type cells, none of these substances had any effects on phototaxis. These results indicate that the action of TRPA1 agonists and antagonists can be readily assessed using the behavior of C. reinhardtii expressing human TRPA1 as an assessment tool.